The Lorenz Energy Cycle: Trends and the Impact of Modes of Climate Variability - Valerio Lembo; Christian Franzke; Qiyun Ma (Tellus A: Dynamic Meteorology and Oceanography, 2021)
The atmospheric circulation is driven by heat transport from the tropics to the polar regions, embedding energy conversions between available potential and kinetic energy through various mechanisms. The processes of energy transformations related to the dynamics of the atmosphere can be quantitatively investigated through the Lorenz energy cycle formalism. Here we examine these variations and the impacts of modes of climate variability on the Lorenz energy cycle by using reanalysis data from the Japanese Meteorological Agency (JRA-55). We show that the atmospheric circulation is overall becoming more energetic and efficient. For instance, we find a statistically significant trend in the eddy available potential energy, especially in the transient eddy available potential energy in the Southern Hemisphere. We find significant trends in the conversion rates between zonal available potential and kinetic energy, consistent with an expansion of the Hadley cell, and in the conversion rates between eddy available potential and kinetic energy, suggesting an increase in mid-latitudinal baroclinic instability. We also show that planetary-scale waves dominate the stationary eddy energy, while synoptic-scale waves dominate the transient eddy energy with a significant increasing trend. Our results suggest that interannual variability of the Lorenz energy cycle is determined by modes of climate variability. We find that significant global and hemispheric energy fluctuations are caused by the El Nino-Southern Oscillation, the Arctic Oscillation, the Southern Annular Mode, and the meridional temperature gradient over the Southern Hemisphere.